COVID-19, Democracies, and (De)Colonialities. Issue 2 (1st December 2020) - Scauso, Marcos S.; FitzGerald, Garrett; Tickner, Arlene B.; Behera, Navnita Chadha; Pan, Chengxin; Shih, Chih-yu; Shimizu, Kosuke
Abstract: Liberal democracies often include rights of participation, guarantees of protection, and policies that privilege model citizens within a bounded territory. Notwithstanding claims of universal equality for "humanity, " they achieve these goals by epistemically elevating certain traits of identity above "others, " sustaining colonial biases that continue to favor whoever is regarded more "human." The COVID-19 pandemic has exacerbated these fault lines, unveiling once more the often-hidden prevalence of inequalities that are based on race, gender, class, ethnicity, and other axes of power and their overlaps. Decolonial theories and practices analyze these othering tendencies and inequalities while also highlighting how sites of suffering sometimes become locations of solidarity and agency, which uncover often-erased alternatives and lessons.